Assessment of infant mortality as a component of public policy in the field of civil health - F.R. Krynychko (Економіка, управління та адміністрування)
Birth rates, health status and infant mortality are important indicators of the quality of life of any country. Analysis of the scientific literature on public administration of the health care system shows that this area has been studied by many scientists, but the assessment of infant mortality as part of public policy has been studied in fragments, which actualizes this study. Thus, the purpose of the article is to investigate the assessment of infant mortality as a component of public policy in the field of civil health. The infant mortality rate was assessed in the following areas: infant mortality rates in the Middle East and North Africa were analysed, and the infant mortality rate in East, West and Central Africa was assessed; estimating the infant mortality rate in South Asia; estimation of the infant mortality rate in the countries of Southeast Asia; estimating the infant mortality rate in Central Asia; estimating the infant mortality rate in East Asia and South-West Asia; the infant mortality rate was estimated in South America and North America; estimating the infant mortality rate in Australia and Oceania; estimating the infant mortality rate in Central America and the Caribbean; estimating the infant mortality rate in Western Europe and Northern Europe; estimation of the infant mortality rate in Southern Europe and Eastern Europe. Having conducted this study to assess the infant mortality rate, it should be noted that a significant number of infant deaths are concentrated in Mauritania, Sudan, India, the Philippines, Cambodia, Tajikistan, Mongolia, Afghanistan, Paraguay, Venezuela, Nauru, Dominican Republic and the Dominican Republic.